2010
DOI: 10.1091/mbc.e09-07-0567
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA Activator GEF-H1/Lfc Is a Transforming Growth Factor-β Target Gene and Effector That Regulates α-Smooth Muscle Actin Expression and Cell Migration

Abstract: TGFβ induces various responses, including Rho signaling. How TGFβ stimulates Rho is poorly understood. Our data indicate that GEF-H1 is a target and effector of TGFβ to regulate Rho signaling, gene expression, and cell migration, suggesting that it represents a new marker and possible therapeutic target for degenerative and fibrotic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 68 publications
4
82
0
3
Order By: Relevance
“…Third, we showed that cell motility induced by RASSF1A depletion could be efficiently inhibited by GEFs activating RhoB, while dominant negative RhoBN19 mutant or siRhoB were able to increase cell motility. Noteworthy, in our settings, overexpressing RhoB-GEF, GEF-H1, restrained RASSF1A-induced cell migration, whereas previous studies had assigned a promigratory role to GEF-H1 (29,40). Conversely, GEF-H1 depletion (Fig.…”
Section: Discussionmentioning
confidence: 43%
“…Third, we showed that cell motility induced by RASSF1A depletion could be efficiently inhibited by GEFs activating RhoB, while dominant negative RhoBN19 mutant or siRhoB were able to increase cell motility. Noteworthy, in our settings, overexpressing RhoB-GEF, GEF-H1, restrained RASSF1A-induced cell migration, whereas previous studies had assigned a promigratory role to GEF-H1 (29,40). Conversely, GEF-H1 depletion (Fig.…”
Section: Discussionmentioning
confidence: 43%
“…The latter effect involves induction of cyclin D1, mediated by RhoA, and requires the Y-box transcription factor ZONAB. Recently, GEF-H1 was also identified as a key regulator of smooth muscle expression and fibrotic processes in retinal pigment epithelium (73). Interestingly, GEF-H1 is also a target of the proliferative MEK/ERK pathway (13,31).…”
Section: Discussionmentioning
confidence: 99%
“…As Xlfc-MO has no effect on tissue stiffness and does not perturb Xenopus development, it is unlikely that Xlfc regulates the stiffness changes observed in the Xenopus embryo . RhoGEF H1/Lfc is involved in regulating cell contractility during mitosis (Bakal et al, 2005), spine formation during dendrite formation (Ryan et al, 2005) and is a gene target of TGF signaling (Tsapara et al, 2010). Much work remains to identify these roles, whether they require reduced microtubule mass or other triggering mechanisms, using both in vitro and in vivo systems.…”
Section: Molecular Contribution Of the Cytoskeleton To Embryonic Tissmentioning
confidence: 99%